2018
DOI: 10.1021/acs.jnatprod.7b00518
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Prenylated Phenylpropenols and Coumarin Derivatives from Murraya exotica

Abstract: Three new prenylated phenylpropenols, exotiacetals A-C (1-3), 10 new coumarin derivatives, exotimarins A-I (4-13), and 35 known analogues (14-48) were isolated from the roots of Murraya exotica. The absolute configurations of the new compounds were assigned via comparison of their specific rotations, single-crystal X-ray diffraction data, Mosher's method, the ECD exciton coupling method, comparison of experimental and calculated ECD data, and the ECD data of the in situ formed transition metal complexes. Compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…A further investigation on the 95% aqueous EtOH extract of the roots allowed the obtainment of new coumarins, together with other bioactive molecules. The compounds were tested for their inhibitory effect on NO production and compound 103 ( Figure 36 In 2018, Liu et al identified ten new coumarin derivatives (3 monomers and 7 dimers) isolated in a phytochemical study on Murraya exotica, a dwarf tree that is native of the tropical and subtropical areas of Asia and traditionally used in the treatment of inflammatory-related diseases [147]. Previous studies had shown that the main active components in M. exotica were coumarins; also bis-coumarins were isolated from the plant.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…A further investigation on the 95% aqueous EtOH extract of the roots allowed the obtainment of new coumarins, together with other bioactive molecules. The compounds were tested for their inhibitory effect on NO production and compound 103 ( Figure 36 In 2018, Liu et al identified ten new coumarin derivatives (3 monomers and 7 dimers) isolated in a phytochemical study on Murraya exotica, a dwarf tree that is native of the tropical and subtropical areas of Asia and traditionally used in the treatment of inflammatory-related diseases [147]. Previous studies had shown that the main active components in M. exotica were coumarins; also bis-coumarins were isolated from the plant.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…In 2018, Liu et al identified ten new coumarin derivatives (3 monomers and 7 dimers) isolated in a phytochemical study on Murraya exotica , a dwarf tree that is native of the tropical and subtropical areas of Asia and traditionally used in the treatment of inflammatory-related diseases [ 147 ]. Previous studies had shown that the main active components in M. exotica were coumarins; also bis-coumarins were isolated from the plant.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Although 24 could not be isolated in a pure form, a sample of pure (±)-exotine A ( 1 ) was obtained via reverse-phase HPLC, eluting with MeCN:H 2 O (35:65 → 50:50, 90 min) and recrystallized (MeOH–CHCl 3 ) to afford pure (±)-exotine A as pale yellow needles. MP 246–247 °C (lit . mp 249–250 °C).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, 1 and 2 possess a coumarin-substituted cyclohepta­[ b ]­indole skeleton, a substructure that was previously unknown among natural products; however, the cyclohepta­[ b ]­indole ring is a common motif found in both natural products and other biologically active molecules . A plausible proposal for the biosynthesis of 1 and 2 was advanced by the Jiang group that posited that 1 and 2 arise from a Diels–Alder reaction between the β-deydroprenylindole 6 and either trans -dehydroosthol ( 3 ) or gleinadiene ( 4 ), each of which is a natural product identified in M. exotica extracts, to give the respective cycloadducts 7 and 8 (Scheme ). Subsequent ring expansion via a 1,2-alkyl migration, which is well-precedented for 3,3-disubstituted and 3,3-spiroindolinenes, then leads to 1 and 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in vivo studies revealed that compound (4m) could inhibit AA-induced rat ankle joints. Yong Jiang et al [68] isolated three new prenylated phenylpropenols, exotiacetals A-C (1-3), 10 new coumarin derivatives, exotimarins A-I (4-13), and 35 known analogs (14-48) from the roots of Murraya exotica. The absolute configurations of the new compounds were characterized through comparison of their specific rotations, single-crystal X-ray diffraction data, Mosher's method, the ECD exciton coupling method, comparison of experimental and calculated ECD data, and the ECD data of the in situ formed transition metal complexes.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%